Diagnóstico operacional de lagoas de estabilização - Silva Filho, Pedro Alves da (2007)
This work intends to develop an approach based through scientific criteria in the operational diagnosis of ponds of stabilization, starting from analyses accomplished in loco and in laboratory of 78 systems of sewer treatment through ponds of stabilization in the State of Rio Grande do Norte. The objectives of the research are: to map, to evaluate and to diagnose the operational acting of the ponds of stabilization of the state of Rio Grande do Norte, through visits in loco and analyses laboratory; to build a SIG, through the map rain, locate the points of releases of sewages of the systems of existent ponds in Rio Grande do Norte, as well as operational data and his/her respective efficiency diagnosis in the removal of BOD and Coliforms Termotolerantes; to evaluate, in real scale, three systems of ponds of stabilization of RN in the operational efficiency for the parameters BOD5, COD, pH, Temperature, OD and Coliforms Termotolerantes. Of 78 ETEs of appraised RN just, 9% or 7 had maximum concepts in what concerns the removal of BOD and Coliforms Termotolerantes and 41% or 32, they had the worst concepts in term of operational efficiency. The flowing concentrations ETEs of RN of BOD and Coliforms were of 410mg/L and 2,50x107UFC/100ml, the predominant configuration is of the type F1+M1+M2, the relationship BOD/COD revealed for the sewer tributary characteristic biodegradable high. For the study of case of 3 ETEs, the best operational efficiencies in decreasing order were: Cidade (Municipal district), it Roça (State) and São Miguel (SAAE). The removals of final BOD were 51,6mg/L; 108,27mg/L and 62,6mg/L, tends efficiency of 82%; 74% and 81%. In term of coliforms removal in the final effluentes were 1,90x103UFC/100ml; 1,50x104UFC/100ml and 3,10x104UFC/100ml, tends efficiencies of 99,99%; 99,95% and 99,90%. In what it concerns the practice of agricultural reúso of cultures consumed raw, none of 3 ETEs assisted the parameters of the Resolution CONAMA 357/05, for other reúso practices, all assisted the categories B and C of OMS. For release in body receiving ETE Cidade just, they assist the demands of the resolution of CONAMA 357/05, by study of purification solemnity of the receiving body. The maintenance lack and operation; exclusive operator in ETEs and operation knowledge was the contributory factors for the operational fall in appraised ETEs of RN